ADR EduCentre: unlocking the secrets of learning alternative dispute resolution / Nur Ezan Rahmat ... [et al.] - Rahmat, Nur Ezan; Mohd Zain, Muhamad Ikhwan; Ilias, Ibtisam@Ilyana; Irwin Ooi, Ui Joo; Randawar, Daleleer Kaur; Safei, Suaida (UiTM Press, 2024)
adopting technology while learning Alternative Dispute Resolution (ADR), students are encouraged to embrace new tools and platforms that facilitate the resolution process. This includes learning how to effectively use online platforms through the introduction of a website known as ADR EduCentre as the ultimate hub for them. ADR EduCentre provides students with a comprehensive range of resources and interactive learning materials to enhance their understanding of ADR. This webpage can also be a platform to exchange ideas for research collaboration with other researchers, for professional networking, and as a valuable resource for accessing relevant research materials and references to support their work. By using doctrinal library-based research, this article aims to explore the various ways in which the website can benefit students in their pursuit of mastering their academic journey. The research found that ADR EduCentre offers students access to a vast collection of case studies, articles, and scholarly publications related to ADR. This wealth of information allows students to deepen their knowledge and gain insights from real-life examples and expert opinions. Overall, ADR EduCentre serves as an invaluable resource for students looking to excel in their studies and other skills. By combining theoretical knowledge with practical application, it is hoped that ADR EduCentre may equip students with a well-rounded understanding of ADR methods, preparing them for success in their future careers.